2017
DOI: 10.1016/j.diabres.2017.01.012
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of overweight and obesity in 5529 adolescents with type 1 diabetes: The T1D Exchange Clinic Registry

Abstract: Aims To describe the prevalence of overweight and obesity in adolescents with type 1 diabetes (T1D) and to examine the associations among socio-demographic, clinical, and self-management factors by weight status. Methods We analyzed baseline data obtained from 5,529 adolescents with T1D (mean age=15.4±1.4 years, 51.8% male, 77.9% white, mean HbA1c=8.7±1.8%; 72 mmol/mol) from the T1D Exchange Clinic Registry. We examined correlates of weight status using multinomial logistic regression analyses. Results Ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
83
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(93 citation statements)
references
References 47 publications
(62 reference statements)
8
83
2
Order By: Relevance
“…The T1D Exchange recently documented that 36% of adolescents with T1D are overweight/obese [20, 21••], which is consistent with the SEARCH for Diabetes in Youth Study [22] and other US T1D samples [23, 24] but higher than the general population [25]. In addition, Canadian and Polish studies of children and adolescents with T1D found that 35 and 30%, respectively, were overweight/obese [26, 27].…”
Section: Weight Status In Type 1 Diabetessupporting
confidence: 58%
See 3 more Smart Citations
“…The T1D Exchange recently documented that 36% of adolescents with T1D are overweight/obese [20, 21••], which is consistent with the SEARCH for Diabetes in Youth Study [22] and other US T1D samples [23, 24] but higher than the general population [25]. In addition, Canadian and Polish studies of children and adolescents with T1D found that 35 and 30%, respectively, were overweight/obese [26, 27].…”
Section: Weight Status In Type 1 Diabetessupporting
confidence: 58%
“…Many studies have shown that girls and women with T1D are more likely to be overweight and/or obese than are boys and men [21••, 24, 27, 28]. However, Duca and colleagues recently reported that 68 and 59% of men and women were in the overweight/obese weight categories, respectively, with more men classified as obese and more women as overweight [29].…”
Section: Biopsychosocial Factors Related To Weight Statusmentioning
confidence: 99%
See 2 more Smart Citations
“…In fact, there is much more overlap than those classic divisions suggest. A database of >5500 adolescents with type 1 diabetes found that 23% were overweight and 13% were obese 28. Furthermore, in youth with type 2 diabetes, the mean age of onset is 13.5 years 29.…”
Section: Discussionmentioning
confidence: 99%